THE ARMENIAN GENOCIDE: INTERNATIONAL LEGAL AND POLITICAL AVENUES FOR TURKEY’S RESPONSIBILITY - Kuyumjian, Aram (Revue de droit de l'Université de Sherbrooke, 2011)
The significance of the Armenian genocide on current affairs cannot be undermined. While it has undoubtedly made its mark on the Armenian people, this genocide has also had further reaching significance. Turkey, as the successor state of the Ottoman Empire, successfully avoided responsibility for its culpability for over several generations, and its example has been considered the foreshadowing for subsequent genocides spanning from the Holocaust to the present-day genocide in Darfur. This paper begins by examining why customary international law governing state responsibility has not been applied. It also analyses the role that international Realpolitik has played in exonerating Turkey and its agents. Viable international legal and political avenues, based on current legislation and jurisprudence, are proposed as a mechanism for enforcing the principle of state responsibility and for implementing reparation.